Nutritional management of surgical newborns and infants in the acute phase and during follow up - Fabio Mosca (PAGEPress Publications, 2018)
The neonatal period represents a crucial stage of life since it is characterized by the development of organ structure and function. Early life is particularly susceptible to environmental factors through a programming effect. As a result, inadequate nutrition in early life leads to long-term mental and physical developmental alterations and increased mortality and morbidity. In this review, we will summarize available evidence with a particular focus on metabolic responses to surgical trauma, nutritional strategies that can be implemented in surgical infants and specific barriers to nutritional support after surgery.